Prints from Elbląg among the collections of the Copernicus Library in Toruń: formal analysis - Urbaniak, Irena (Folia Toruniensia, 2013)
The article includes a formal analysis of Elbląg prints from the 16th- 18th centuries, which are now part of the collection of the Copernicus Library in Toruń. It discusses in detail Elbląg’s printing industry of the period and introduces the owners of printing houses. The articles also addresses the languages in which the texts were printed and their chronological scope. The first printer in Elbląg was Wolfgang Dietmar, who worked in Elbląg for a short time – merely 6 years (1558-1564). Elbląg’s printing industry flourished at the beginning of the 17th century, when Wendelin I Bodenhausen arrived in Elbląg when the city was in its prime. The printing house belonged to the Bodenhausen family for over 40 years. Next, the printing house became the property of the Korell family. After Achacy II Korell died without an heir, the printing house was sold to the Preuss family of merchants who were related to the Korells and remained their property for over 50 years. Other significant printers from Elbląg were Johann Gottlieb Nohrmann and Friedrich Traugott Hartmann. In the period under discussion, books in Elbląg were printed in three languages: Polish, German and Latin. The majority of prints analyzed in the article were published in Latin. It has been established that until 1772 Elbląg’s printing houses issued 1679 prints, merely 77 of which are included in the collections of the Copernicus Library.